The relationship between parental war status and socioemotional functioning of offspring of Croatian war veterans - Lovorka BRAJKOVIĆ; Dora KORAĆ; Dajana ALIĆ; Vanja KOPILAŠ (Journal of Health and Social Sciences)
Introduction: Family dysfunction and inability to adequately respond to parental demands of veterans due to active participation in war and the presence of war-related PTSD has been linked to numerous psychosocial and behavior problems of their offspring. The aim of this study was to examine the relationship between parental war status, and certain aspects of socioemotional development of their children, i.e. emotional competence, and attachment styles. Methods: Our sample consisted of 141 participants (female: 51.1%, mean age: 25.78), of which 53 were offspring of veterans with PTSD, 39 were offspring of veterans without PTSD, and 49 came from non-veteran families. A structured questionnaire consisted of sociodemographic questions, The Emotional Competence Questionnaire, The Revised Adult Attachment Scale, and Inadequate parental behavior questionnaire. Results: Children of war veterans exhibited greater difficulties in understanding, expressing, and regulating their own emotions in comparison to children of non-veterans. Higher presence of anxious attachment style, lower levels of close and dependent style, and more frequent inadequate parental behavior during childhood were found in offspring of veterans with war-related PTSD. Discussion: The offspring of war veterans showed lower emotional competence and a more pronounced anxious attachment style. These findings emphasize the importance of developing interventions and programs for offspring of war veterans that aim to improve their ability to establish close relationships and regulate emotions adequately.